2017
DOI: 10.1080/10428194.2017.1285026
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of initial parenchymal central nervous system involvement in systemic aggressive B-cell lymphoma

Abstract: Central nervous system (CNS) involvement in systemic B-cell non-Hodgkin lymphoma (B-NHL) at diagnosis (sysCNS) is rare. We investigated the outcome of 21 patients with sysCNS, most commonly diffuse large B-cell lymphoma, treated with high dose methotrexate (HD-MTX) and R-CHOP. The median number of cycles of HD-MTX and R-CHOP was 4 (range 1-8) and 6 (range 0-8), respectively. Consolidative whole brain radiotherapy (WBRT) was given to 33% (7/21) patients. With a median follow-up of 44 months the 3-year progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…After achieving remission, whole brain radiotherapy was given for consolidation. The complete response rate 57%, with 3 years PFS and OS 45% (95% CI 34-56%) and 49% (95% CI 38-60%); [11]Those were comparable to gures reported here.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…After achieving remission, whole brain radiotherapy was given for consolidation. The complete response rate 57%, with 3 years PFS and OS 45% (95% CI 34-56%) and 49% (95% CI 38-60%); [11]Those were comparable to gures reported here.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, several studies explored the effectiveness of non-transplant regimens in SCNSL and indicated that this can be an effective treatment for SCNSL. [11][12][13] Nijland et al retrospectively investigated the outcome of SCNSL patients treated with HD-MTX and R-CHOP(rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone regimen) without ASCT, the 3-year OS was 49% which was comparable to patient outcomes with more intensive treatment including ASCT. [11] Moreton et al carried out a pilot study using IDARAM regimen in 16 SCNSL among which 12 achieved CR, seven remained CR at median follow-up of 24 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our data support CNS staging as part of the routine staging work-up in patients at high risk of SCNS based on current risk models,(4, 9, 11) as patients with concurrent CNS and systemic disease at initial diagnosis may have better outcomes with intensive treatment strategies containing both HDMTX and anthracycline-based immunochemotherapy. (26)…”
Section: Discussionmentioning
confidence: 99%
“…Based on our identification of the ectodomain of HLA-DRB1 in the CSF of PCNSL patients, we suggest an alternative mechanism of cancer-associated immune evasion, which, to our knowledge, has not been described so far. The combined loss of HLA class I and HLA class II antigens is known to occur at a high frequency in PCNSL, thus allowing immune escape [ 44 ]. Until now, the loss or aberrant expression of HLA on the cell surface has mostly been linked to cytosolic retention [ 45 ] or incorrect loading of the antigen-binding groove [ 46 ].…”
Section: Discussionmentioning
confidence: 99%